The Impact of International Intrepreneurship on the Development of Transport - Bukova, Bibiana; Brumercikova, Eva; Kondek, Pavol; Sojcak, Dusan (Communications - Scientific letters of the University of Zilina, 2016)
The article deals with the perspectives for the development of international entrepreneurship and the development of transport. Perspectives were determined based on research and the results of this research are presented in the article.